2022
DOI: 10.1590/1983-1447.2022.20210033
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of adolescents with suicidal behavior with social support networks

Abstract: Objective: To identify the relationships of adolescents with suicidal behavior established with social support networks. Method: Qualitative study addressing ten adolescents with suicidal behavior cared for by a psychosocial care center attending children and adolescents located in southern Brazil. Semi-structured interviews were held in July 2020 via WhatsApp during the COVID-19 pandemic, and data were analyzed according to Minayo’s thematic analysis. Results: Two categories emerged: Dynamics of the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
(22 reference statements)
0
0
1
2
Order By: Relevance
“…This study is not in line with research by Cahya revealing that high social media use is at risk of anxiety and depression [18]. Simoes's research has shown that social support has an impact on suicidal behavior [19]. In line with Rahayu's research, social support through social media has a positive effect on reducing suicidal behavior.…”
Section: Descriptivecontrasting
confidence: 87%
“…This study is not in line with research by Cahya revealing that high social media use is at risk of anxiety and depression [18]. Simoes's research has shown that social support has an impact on suicidal behavior [19]. In line with Rahayu's research, social support through social media has a positive effect on reducing suicidal behavior.…”
Section: Descriptivecontrasting
confidence: 87%
“…2023;14:e-202308 riscos, intensificar recursos para lidar melhor com os eventos estressores e conseguir desfecho positivos frente às situações. (20,21) Estudos têm demonstrado que o pensamento e comportamento suicidas têm uma forte associação negativa com o desempenho acadêmico e apontam a necessidade de programa de intervenção na prevenção de suicídio nos ambientes universitários. (22,23)…”
Section: Discussionunclassified
“…Isso pode levar a uma baixa tolerância à frustração e dificuldade em lidar com conflitos e perdas. (Simões et al, 2022)…”
unclassified